Bending diameter dependence of mode instabilities in multimode fiber amplifier. (6th February 2019) - Zhang, Fangfang; Xu, Haozhen; Xing, Yingbin; Hou, Shaodong; Chen, Yisha; Li, Jinyan; Dai, Nengli; Li, Haiqing; Wang, Yibo; Liao, Lei
Abstract: We systematically investigated the dependence of mode instability (MI) thresholds on bending diameters in ytterbium-doped fiber amplifiers. The MI thresholds of a fiber amplifier, which was based on a multimode ytterbium-doped fiber, were measured at various bending diameters. It is found that the correlation between MI thresholds and fiber bending diameters depends on the operation state of the active fiber. When the multimode active fiber is in the few-mode operation, the MI threshold is successfully raised from 717 W to 1084 W by increasing the fiber bending diameter from 11 cm to 60 cm. When the multimode active fiber operates in quasi-single mode, the MI threshold is raised from 717 W to 953 W by reducing the bending diameter from 11 cm to 8 cm. According to our experiments and previous reports, it is suggested that the influence of changing fiber bending diameter on MI might be closely related to the mode coupling effect.